Adaptation through Collaboration: Evaluating the Emergence of Institutional Arrangements for Catchment Management and Governance in England - Watson, Nigel (International Journal of Water Governance, 2015)
Local-scale collaborative catchment management pilot projects were established in England in 2011 as part of an initiative to improve implementation of the EU Water Framework Directive (WFD), give more control to non-government groups and deliver multiple economic, social and environmental benefits. Local experiences were examined with respect to six criteria: motives and frames; focus and purpose; structures and niches; engagement, power and use of facilitation; deliberation and social learning; and cross-scale institutional linkage. The findings indicate that organisational histories and established power relations among the participants were important influences on the initiation, development and impacts of collaboration. Catchment-scale collaboration did strengthen inter-organisational relationships and did increase support for specific water management activities. However, the full potential of an integrated approach to resource planning and management was not realised during the piloting phase because institutional structures and mechanisms were not established to link collaborative catchment groups with key water and resource governance regimes, including the WFD planning process. Collaborative governance has not taken the place of government-based decision making. However, more limited arrangements are developing for collaborative water management at a catchment scale which are sanctioned by government and, to variable degrees, orchestrated by established and powerful local organisations and groups.